2003
DOI: 10.1038/sj.onc.1206422
|View full text |Cite
|
Sign up to set email alerts
|

Phenoxodiol – an isoflavone analog – induces apoptosis in chemoresistant ovarian cancer cells

Abstract: Interference with the innate apoptotic activity is a hallmark of neoplastic transformation and tumor formation. In this study we characterize the cytotoxic effect of phenoxodiol, a synthetic anticancer drug analog of genestein, and demonstrate the mechanism of action by which phenoxodiol affects the components of the Fas apoptotic pathway on ovarian cancer cells. Primary ovarian cancer cells, isolated from ascitic fluids of ovarian cancer patients, resistant to conventional chemotherapy, undergo apoptosis foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
173
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 175 publications
(182 citation statements)
references
References 41 publications
(35 reference statements)
8
173
0
1
Order By: Relevance
“…We found that SK-N-SH and SK-N-AS expressed high levels of XIAP. These findings correlated with previous studies showing that IAPs are highly expressed in many tumours and contribute to the resistance of cancers to apoptosis (Deveraux et al, 1998;Salvesen and Duckett, 2002;Kamsteeg et al, 2003). Treatment of the neuroblastoma cells with gold(III) porphyrin 1a inhibited the expression of XIAP.…”
Section: Discussionsupporting
confidence: 80%
“…We found that SK-N-SH and SK-N-AS expressed high levels of XIAP. These findings correlated with previous studies showing that IAPs are highly expressed in many tumours and contribute to the resistance of cancers to apoptosis (Deveraux et al, 1998;Salvesen and Duckett, 2002;Kamsteeg et al, 2003). Treatment of the neuroblastoma cells with gold(III) porphyrin 1a inhibited the expression of XIAP.…”
Section: Discussionsupporting
confidence: 80%
“…Protein extraction was done as previously described (Kamsteeg et al, 2003). Briefly, cell pellets were lysed on ice in 1 Â phosphate-buffered saline with 1% NP40, 0.1% SDS and freshly added 20 ml/ml protease inhibitor cocktail (Sigma Chemical, St Louis, MO, USA) and 2 mM phenylmethylsulfonyl fluoride (Sigma Chemical).…”
Section: Protein Preparationmentioning
confidence: 99%
“…A quantity of 20 mg of each protein sample was denatured in sample buffer and subjected to 12% SDS-polyacrylamide gel electrophoresis (PAGE) as previously described (Kamsteeg et al, 2003). The following antibodies were used: rabbit antihuman MyD88 (1:1,000), mouse anti-human IkBa (1:1,000), rabbit anti-human IKKa (1:1,000), rabbit anti-human IKKb (1:2,000) and rabbit anti-human b-actin (1:10,000).…”
Section: Sds-page and Western Blotsmentioning
confidence: 99%
See 1 more Smart Citation
“…XIAP reagents have been identified and are in preclinical as well as clinical trial testing. 4,5,16,17 XIAP expression in non-small cell lung carcinoma has been reported in cell culture and animal models. [18][19][20][21] However, immunohistochemical studies specifically addressing XIAP expression in human lung adenocarcinoma and alveolar hyperplasias are lacking.…”
mentioning
confidence: 99%